Akachan to Boku: Tantangan Ayah Tunggal di Jepang - Dinda Maryanti; I Wayan Sadyana; Gede Satya Hermawan (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to describe the form of the challenges of the character Harumi Enoki in the manga Akachan to Boku Volume 1 as a single parent. The method used is descriptive qualitative with a family sociology approach. Data collection was carried out using the observation method and note taking techniques and then analyzed using the structural functional theory proposed by Durkheim. The result of the study show that father as a single parents have two challenges. The first challenge came from the child who was raised by Harumi Enoki. The challenges from Harumi Enoki’s children are in the from of feelings of jealousy and fights. The second challenge faced by Harumi Enoki is the social view of society towards the way of parenting that is carried out by Harumi Enoki. Society in Japan consider that single parent, especially single father do not have to ability to raise and educate children.